THERMODYNAMIC PROPERTIES OF WATER DESORPTION OF SOYBEAN BRAN - Corrêa, Isabel Cristina Machado; Noreña, Caciano P. Zapata (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
The differential and integral thermodynamic properties (enthalpy, entropy, Gibbs free energy, temperature isokinetic and spreading pressure) of soybean bran were determined. Experimental data obtained from the literature were adjusted appropriately by GAB equation (R2>0.95), whose parameters were used to estimate the thermodynamic properties of desorption of soybean bran. The differential enthalpy and entropy increased with decreasing equilibrium moisture content and the isokinetic temperature confirmed the linear chemical compensation between the enthalpy and entropy and the process was enthalpy driven. The spreading pressure increased with increasing water activity. The integral enthalpy decreased with increasing equilibrium moisture content, whereas the integral entropy increased, but negative values, reaching up to -0.02 kJ/mol.K.